Jade Chemicals, Inc. - Alegre, Bernardo R.; Dulay, Renato C.; Juadiong, Jerome T. (Diliman, Quezon City College of Engineering, 1965)
Capacity: 24 tons per 24-hour day -- Land area: 5242 sq. m. -- Fixed capital investment: 7,469,163 -- Operating cost at maximum production: 2,588,922 -- Sales at maximum production: 5,184,000 -- Pay-off time: 5-6 years -- Break-even point: 9.2 tons/day -- Shut-down point: 2.88 tons/day
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical plants; Furfural